The Transthyretin/Oleuropein Aglycone Complex: A New Tool against TTR Amyloidosis - Francesco Bemporad; Manuela Leri; Matteo Ramazzotti; Massimo Stefani; Monica Bucciantini (Pharmaceuticals, 2022)
The release of monomers from the homotetrameric protein transthyretin (TTR) is the first event of a cascade, eventually leading to sporadic or familial TTR amyloidoses. Thus, ligands able to stabilize TTR and inhibit monomer release are subject of intense scrutiny as potential treatments against these pathologies. Here, we investigated the interaction between TTR and a non-glycated derivative of the main olive polyphenol, oleuropein (OleA), known to interfere with TTR aggregation. We coupled fluorescence studies with molecular docking to investigate the OleA/TTR interaction using wild-type TTR, a monomeric variant, and the L55P cardiotoxic mutant. We characterized a fluorescence band emitted by OleA upon formation of the OleA/TTR complex. Exploiting this signal, we found that a poorly specific non-stoichiometric interaction occurs on the surface of the protein and a more specific stabilizing interaction takes place in the ligand binding pocket of TTR, exhibiting a KD of 3.23 ± 0.32 µM, with two distinct binding sites. OleA interacts with TTR in different modes, stabilizing it and preventing its dissociation into monomers, with subsequent misfolding. This result paves the way to the possible use of OleA to prevent degenerative diseases associated with TTR misfolding.